2011
DOI: 10.1182/blood-2011-06-362392
|View full text |Cite
|
Sign up to set email alerts
|

The utility of plasma vascular endothelial growth factor levels in the diagnosis and follow-up of patients with POEMS syndrome

Abstract: The POEMS syndrome is associated with elevated vascular endothelial growth factor (VEGF) levels. Several studies have compared serum VEGF levels between POEMS patients and other disease entities showing higher serum VEGF in POEMS syndrome; however, it is unknown whether serum levels are reliable and reproducible given variable platelet release of VEGF. We therefore compared plasma levels of VEGF in 29 patients with POEMS syndrome with those of other disorders (n = 76). We demonstrated that plasma VEGF levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
187
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(193 citation statements)
references
References 21 publications
1
187
2
3
Order By: Relevance
“…The requirements set forth in Table I are designed to retain both sensitivity and specificity, potentially erring on the side of specificity. Making the diagnosis can be a challenge, but a good history and physical examination followed by appropriate testing-most notably radiographic assessment of bones [40][41][42] measurement of VEGF [13,17,20,43,44], and careful analysis of a bone marrow biopsy [39]-can differentiate this syndrome from other conditions like CIDP, monoclonal gammopathy of undetermined significance (MGUS) neuropathy, and immunoglobulin light chain amyloid neuropathy. A high platelet count is seen in 54% of POEMS patients as compared to 1.5% of patients with CIDP [45].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The requirements set forth in Table I are designed to retain both sensitivity and specificity, potentially erring on the side of specificity. Making the diagnosis can be a challenge, but a good history and physical examination followed by appropriate testing-most notably radiographic assessment of bones [40][41][42] measurement of VEGF [13,17,20,43,44], and careful analysis of a bone marrow biopsy [39]-can differentiate this syndrome from other conditions like CIDP, monoclonal gammopathy of undetermined significance (MGUS) neuropathy, and immunoglobulin light chain amyloid neuropathy. A high platelet count is seen in 54% of POEMS patients as compared to 1.5% of patients with CIDP [45].…”
Section: Diagnosismentioning
confidence: 99%
“…A high platelet count is seen in 54% of POEMS patients as compared to 1.5% of patients with CIDP [45]. Helpful cutoffs for plasma and serum VEGF levels to diagnosis POEMS syndrome are 200 pg mL 21 (specificity 95%; sensitivity 68%) [20] and 1,920 pg mL 21 (specificity 98%; sensitivity 73%) [46], respectively. Wang et al have identified N-terminal propeptide of type I collagen as a novel marker for the diagnosis of patients with POEMS [46].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, VEGF levels exhibit the strongest correlations with disease activity in POEMS syndrome 3, 15. Plasma and serum VEGF levels of 200 pg/mL and 1,000 pg/mL, respectively, are considered to be diagnostic cut‐off values for POEMS syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we obtained further strong evidence to support this diagnosis; that is, a markedly raised VEGF level; the patient's plasma and serum VEGF levels were 555 pg/mL and 1530 pg/mL, respectively. It has been reported that a plasma VEGF level of 200 pg/mL exhibits 95% specificity and 68% sensitivity for diagnosing POEMS syndrome 3. According to the Japanese diagnostic criteria for POEMS syndrome issued by the Japan Intractable Diseases Information Center, a significantly elevated VEGF level is defined as a serum level of >1000 ng/mL 4.…”
Section: Differential Diagnosis Examinations and Treatmentmentioning
confidence: 99%